2020
DOI: 10.1371/journal.pone.0232207
|View full text |Cite
|
Sign up to set email alerts
|

Data linkage and computerised algorithmic coding to enhance individual clinical care for Aboriginal people living with chronic hepatitis B in the Northern Territory of Australia – Is it feasible?

Abstract: BackgroundChronic hepatitis B (CHB) is endemic in the Aboriginal population of Australia's Northern Territory (NT). However, many people's hepatitis B virus (HBV) status remains unknown. Objective 1. To maximise the utility of existing HBV test and vaccination data in the NT by creating a linked dataset and computerised algorithmic coding. 2. To undertake rigorous quality assurance processes to establish feasibility of using the linked dataset and computerised algorithmic coding for individual care for people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The “one stop liver shop” has been shown to improve the cascade of care in these communities, but there remains a significant number of individuals who are not yet diagnosed [ 29 ]. Data linkage and coding has attempted to improve identification of cases; however, many individuals do not have hepatitis B testing results [ 30 ]. A targeted strategy is likely needed for those who are pregnant to ensure hepatitis B is diagnosed and care is received.…”
Section: Discussionmentioning
confidence: 99%
“…The “one stop liver shop” has been shown to improve the cascade of care in these communities, but there remains a significant number of individuals who are not yet diagnosed [ 29 ]. Data linkage and coding has attempted to improve identification of cases; however, many individuals do not have hepatitis B testing results [ 30 ]. A targeted strategy is likely needed for those who are pregnant to ensure hepatitis B is diagnosed and care is received.…”
Section: Discussionmentioning
confidence: 99%
“… 21 These studies, in combination with the present data, suggest that the current HBV vaccine is sufficient to protect against chronic infection (and possibly symptomatic acute infection, as demonstrated in a study of Alaska Native people 28 ), but not against acute infection in populations with a serotype mismatch, although a study of vaccinated Indigenous individuals living in Western Australia found a small number of people who developed CHB. 37 A recent data linkage study found that 94.1% of people born after 1990 in five NT Indigenous communities received a full vaccination course, 38 further suggesting that implementation issues are unlikely to explain the decrease in vaccine efficacy observed.…”
Section: Discussionmentioning
confidence: 99%
“…This has allowed more complete interpretation of one’s serological status. This is important as complete serological assessment has been shown to be suboptimal in our region but is currently being addressed with data linkage and computerised coding [ 12 ].…”
Section: Discussionmentioning
confidence: 99%